PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTU CANVA PADA MATERI KEBERAGAMAN BUDAYA INDONESIA UNTUK SISWA KELAS V SEKOLAH DASAR - Emilia Putri; Zaka Hadikusuma Ramadan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of the research is to determine the development of Canva-assisted learning media on Indonesian cultural diversity material for fifth grade elementary school students and to determine the validity of the Canva-assisted learning media that has been created. The methodology used is R&D with the ADDIE development model. The development target is 21 students, 10 of whom are 2 material experts, 2 language experts, and 2 media experts. The research instruments used were material validation questionnaires, language validation questionnaires, media validation questionnaires and teacher response questionnaires and student response questionnaires. The research results obtained material validation of 94.06% in the